Analisis Sisa Lebih Perhitungan Anggaran (SiLPA) Pada Anggaran Pendapatan Dan Belanja Daerah (APBD) Kabupaten Muaro Jambi Tahun Anggaran 2015-2019 - Sri Rosmawati (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT STIE-GRAHA KARYA MUARA BULIAN, 2021)
APBD calculation is the responsibility of local governments for all programs and activities that have been budgeted for in the APBD. On the one hand, the APBD describes the calculation of estimated and realized expenditures, and on the other hand, describes the calculation of the estimated and realization of Regional Revenue in financing regional programs and activities in one budget. The relevance of data and information on budget differences with the realization is also a form of government accountability for the management of public funds. SiLPA is the excess of realized budget revenues and expenditures during one budget period. SiLPA is a source of internal local government revenue which is used to fund current year's activities. SiLPA is used as an indicator of efficiency, because SiLPA will be formed if there is a surplus in the APBD and realization. This study aims to determine the Excess Budget Calculation (SiLPA) and the components that cause the SiLPA. The research method used in this research is descriptive quantitative. The data used in this research is secondary data in the form of APBD data from http://www.djpk.kemenkeu.go.id/. The SiLPA in Muaro Jambi Regency during the 2015-2019 period experienced fluctuations. The factor that caused the Excess Budget Calculation (SiLPA) in Muaro Jambi Regency during the 2015-2019 period was the exceeding of the Regional Original Income (PAD) which exceeded the target. PAD that exceeds this target comes from local taxes. The remaining Regional Expenditures during the 2015-2019 period occurred only in 2018 which came from capital expenditures.